An approach to supporting young people with autism spectrum disorder and high anxiety to re-engage with formal education – the impact on young people and their families. Issue 4 (2nd October 2018) - Preece, David; Howley, Marie
Abstract: School refusal is an important factor impacting upon poor outcomes for adolescents and youth. Individuals with autism spectrum disorder (ASD) experience characteristic difficulties regarding social interaction and communication, rigidity of thinking and sensory sensitivities. These difficulties, coupled with the heightened anxiety that many on the spectrum experience, place them at particular risk of school refusal. This study investigates activity undertaken in one UK local authority, where provision was developed to help such students to re-engage with formal education. Data were collected at three points through the first year of the provision's existence. Findings show all students were successfully supported to attend the provision and re-engage with formal education. Factors supportive of re-engagement are presented and considered in the light of an ecological model of support for school refusers and what is considered as 'good practice' in autism education. It is suggested that the factors identified are indicative of good practice across both areas of activity.